Accounting for voluntary hospices in England: A business model perspective. (July 2018) - Haslam, Colin; Tsitsianis, Nick; Theodosopoulos, Grigorios; Lee, Edward
Highlights: Voluntary hospices in England provide over seventy percent of palliative bed capacity for end of life patients. The provision of hospice care can be accounted for within a business model framework of analysis. Interviews with key stakeholders reveals the changing nature of activities carried out within the hospice business model. Financial numbers reveal the impact of stakeholder relations on financial viability. Abstract: This paper accounts for the sustainability of voluntary hospices in England that provide palliative end of life care for patients. A critical evaluation of the challenges facing hospices in England can be located within a 'descriptive business model' that makes visible stakeholder relations. Changes to these stakeholder relations, and how they impact upon the viability of the hospice business model, can be captured within a 'narratives and numbers' investigative framework. Interviews with senior clinical and non-clinical managers in four hospices provide rich 'narratives' that reveal how the hospice business model is evolving. Whilst financial disclosures extracted from hospice financial statements generate 'numbers' which can be employed to explore the impact of changes in stakeholder relations upon financial viability. Our argument is that the hospice business model depends upon sustaining a complex network of stakeholder relations in order to maintain operational and financial viability.